2017
DOI: 10.3892/ol.2017.7531
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of matrine on cancer stem like cells isolated from the human liver cancer SMMC‑7721 cell line

Abstract: Abstract. The existence of cancer stem cells (CSCs) or cancer stem-like cells (CSLCs) is regarded as the cause of tumor formation and recurrence. Matrine has been reported to exhibit antitumor effects in cancer cells. In the present study, a preliminary study was performed on the mechanisms of matrine on hepatocellular carcinoma (HCC) stem-like cells. The HCC SMMC-7721 cell line was cultured in tumor stem cell-specific medium to form spheres, and different concentrations (1, 2 and 5 mg/kg) of cisplatin were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Current researches demonstrated that PC had magnificent perspective in cancer treatment both in vitro and in vivo. Wang Y (Wang et al, 2009) discovered that phycocyanin from Porphyrayezoensis could kill human liver cancer cell SMMC-7721 in vitro. Li B reported that phycocyanin could remarkably prohibit the growth and development of human lung cancer A549 cells on a time-and dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Current researches demonstrated that PC had magnificent perspective in cancer treatment both in vitro and in vivo. Wang Y (Wang et al, 2009) discovered that phycocyanin from Porphyrayezoensis could kill human liver cancer cell SMMC-7721 in vitro. Li B reported that phycocyanin could remarkably prohibit the growth and development of human lung cancer A549 cells on a time-and dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Total alkaloids present in S. alopecuroides have been shown to impede growth; treatment with 8.75 mg/mL of total alkaloids of S. alopecuroides caused cell death in >50% of HeLa cells, and the cell death rate increased with longer incubation. Additionally, several active ingredients of S. alopecuroides, including aloperine [19], cytosine [20,21] matrine [22][23][24][25], oxymatrine [26][27][28], sophoridine [29,30], oxysophoridine [31], and sophocarpine [32], are also known to impede tumor cell growth.…”
Section: Effect On Tumor Cell Growthmentioning
confidence: 99%
“…It inhibited the proliferation of LCSCs in a dose-dependent manner, and upregulated the levels of CAR, laminin, E-cadherin as well as fibronectin in LCSCs which led to the reduction of cell adhesion and the increase of cell apoptosis. All in all, matrine may inhibit LCSCs by regulating CAR signal transduction [50].…”
Section: Other Relevant Signaling Pathwaysmentioning
confidence: 99%